1985
DOI: 10.1002/pros.2990070408
|View full text |Cite
|
Sign up to set email alerts
|

Changes of cytosol proteins in the ventral and dorsolateral prostates of rats during sexual maturation: Immature prostate‐abundant proteins as detected by polyacrylamide gel electrophoreses

Abstract: Cytosol proteins in the ventral and dorsolateral prostates of rats from four to 31 weeks of age were analyzed by SDS‐electrophoresis. By comparing the relative contents (% of the total protein), it was found that in addition to the known major proteins which became abundant with age, there were several species abundant in the sexually immature prostates: (1) Ventral prostate: two kinds of secretory proteins with apparent molecular weights of about 31,000 (31K) and 67,000 (67K) and five kinds of nonsecretory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…*P<005 compared with controls of the same age (Student's Mest). & Higgins, 1986) and prostate (Heyns et al 1978;Higgins et al 1982;Wada et al 1985) show similar marked changes as a function of age. In mouse pro¬ state (Mills et al 1987 ), seminal vesicle (Normand et al 1989) and epididymis (Lefrançois et al 1992), specific proteins are detectable in young animals (10-20 days) and begin to accumulate in large amounts between 20 and 40 days.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…*P<005 compared with controls of the same age (Student's Mest). & Higgins, 1986) and prostate (Heyns et al 1978;Higgins et al 1982;Wada et al 1985) show similar marked changes as a function of age. In mouse pro¬ state (Mills et al 1987 ), seminal vesicle (Normand et al 1989) and epididymis (Lefrançois et al 1992), specific proteins are detectable in young animals (10-20 days) and begin to accumulate in large amounts between 20 and 40 days.…”
Section: Discussionmentioning
confidence: 57%
“…The synthesis and secretion of tissue-specific marker pro¬ teins during development have received limited atten¬ tion. The appearance of androgen-dependent proteins during the development of the seminal vesicle (Kistler et al 1981 ;Fawell & Higgins, 1986;Normand et al 1989), prostate (Heyns et al 1978 ;Higgins et al 1982 ;Wada et al 1985;Mills et al 1987è) and epididymis (Faye et al 1980;Kohane et al 1983;Brooks, 1987;Charest et al 1989;Lefrançois et al 1992) seems to be quite variable, and no report exists on the role of androgens in the expression of these proteins during sexual maturation.…”
Section: Introductionmentioning
confidence: 97%
“…Wilson and colleagues [4-61 reported that transferrin and albumin appear to be major cytosol proteins of the Dunning tumor, from which they succeeded in purifying transferrin. We have recently reported that the Dunning tumor resembles the dorsolateral prostate of immature rats in its low contents of zinc and "probasin, " an androgen-dependent protein abundantly localized in the dorsolateral prostate of mature rats [7,8], and that a 41,000-dalton protein was abundant in both the immature dorsolateral prostate and the Dunning tumor [7,9]. On the other hand, comparison of two-dimensional electrophoretic patterns between normal prostate and Dunning tumors suggests an irreversible change in the cytoskeletal protein in the tumor [3].…”
Section: Introductionmentioning
confidence: 99%